2008
DOI: 10.1103/physrevb.77.035203
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced dynamics of muonium centers in Si studied via their precession signatures

Abstract: We studied the influence of the optical excitation on three muonium centers Mu T 0 , Mu BC 0 , and Mu BC + in high resistivity silicon. These investigations were carried out on the spin precession signature of each center as a function of temperature. It is found that photoexcitation resulted in significant enhancements of the depolarization rates of the precession signals as the three muonium centers underwent interactions with photogenerated free carriers. The results are described by a three-state model inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…2, and the applicability for a wide temperature range. The latter advantage is also endorsed by previous photoexcited µSR studies on Si, which found a large photoinduced relaxation in the Mu BC precession not only in the low temperature range continuously down to several Kelvins [18] but also in the high temperatures up to 550 K [19].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…2, and the applicability for a wide temperature range. The latter advantage is also endorsed by previous photoexcited µSR studies on Si, which found a large photoinduced relaxation in the Mu BC precession not only in the low temperature range continuously down to several Kelvins [18] but also in the high temperatures up to 550 K [19].…”
supporting
confidence: 53%
“…The µSR technique has been applied to many semiconductor systems, especially to single crystal Si [13,14]. There have been several µSR studies on illuminated Si wafers, which report a large photoinduced change in the µSR time spectrum [15,16,18,19].…”
mentioning
confidence: 99%
“…Generated electrons and holes interact with Mu in a quite complex mechanism including spin exchange interaction, cyclic charge exchange reaction, and site change reaction. 13,14,16 In addition to the microscopic mechanisms, the carrier recombination lifetime and carrier transport from the illuminated surface influence the relaxation rate. Therefore, although the light-ON spectrum can be fitted well with a single exponential, the relaxation is a convolution of these factors.…”
Section: A Time Spectrummentioning
confidence: 99%
“…To demonstrate the effectiveness of the newly constructed system, we have performed a photo-µSR experiment on silicon, which is known to give a large photo-induced effect. 13,14,16 The experiment has been carried out on a 500-µm thick intrinsic silicon wafer (n-type, R ≈2400 Ω·cm) with 110 crystal axis perpendicular to the surface. One side is polished and is facing the incoming laser light, whereas the other side has an etched surface that faces the muon beam (back-pump geometry).…”
Section: Photo-µsr Experiments On Siliconmentioning
confidence: 99%
See 1 more Smart Citation